Telaah Potensi Reunifikasi Tiongkok Terhadap Taiwan: Tinjauan Teori Attitudinal Factor - Kristoforus Bagas Romualdi; Saefur Rochmat (UIN ALAUDDIN MAKASSAR, 2023)
This study attempts to examine the potential of China's reunification of Taiwan, which has been fought for up until the time of Xi Jinping. The Chinese side has made various efforts to achieve unification, one of which is proposing the